Finite time stabilization of non-autonomous, nonlinear second-order systems based on minimum time principle - My, Dang Van; Minh, Trinh Hoang; Nga, Vu Thi Thuy; Phuoc, Nguyen Doan (Vietnam Journal of Science and Technology, 2021)
This paper proposes a controller design method to stabilize a class of nonlinear, non-autonomous second-order systems in finite time. This method is developed based on exact-linearization and Pontryagin’s minimum time principle. It is shown that the system can be stabilized in a finite time of which the upper bound can be chosen according to the initial states of the system. Simulation results are given to validate the theoretical analysis